Thrombus‐mimicking artifacts in two‐point Dixon MRI: Prevalence, appearance, and severity. Issue 1 (5th July 2016) - Schubert, Tilman; Bannas, Peter; Kinner, Sonja; Sharma, Samir; Holmes, James H.; Rahimi, Mahdi Salmani; Korosec, Frank R.; Reeder, Scott B.
Abstract : Purpose: To evaluate the incidence and severity of potentially thrombus mimicking, flow‐induced misallocation artifacts in a clinical setting. Two‐point "Dixon" fat–water separation methods, with bipolar readout gradients, may suffer from flow‐induced fat–water misallocation artifacts. If these artifacts occur within blood vessels, they may mimic thrombus. Materials and Methods: Two‐point Dixon coronal and axial images acquired in 102 consecutive patients were retrospectively evaluated for the presence of flow‐induced artifacts in arteries and veins. Artifacts were graded on a 3‐point scale (none, mild, severe) by two independent readers. Interreader agreement was evaluated with kappa statistics. Results: Reader 1 reported 63 artifacts in 46 (45%) of the cases (severe in 19 cases, 18.6%). Reader 2 reported 51 artifacts in 43 (42.2%) of the cases (severe in 18 cases, 17.6%). Misallocation of fat and water was apparent in all datasets with severe artifacts, whereas variable signal intensity changes in water and fat images were observed in mild artifacts. Interreader agreement was good for artifacts appearing in coronal images (κ = 0.7) and fair for artifact appearance in axial images (κ = 0.24). Conclusion: Our study shows a high incidence of flow‐induced mild and severe artifacts in a two‐point Dixon method with bipolar readout gradients. This artifact should not be misinterpreted as intravascular thrombus. Level of Evidence: 3 J. Magn. Reson. Imaging 2017;45:229–236.